Peran Dukungan Keluarga Terhadap Pemulihan Anak Korban Pelecehan Seksual Di Daerah Perkotaan Menurut Hukum Dan HAM. - Fadlila Firdausi Aziza (Faculty of Law, University of Mataram, 2025)
This journal examines the role of family support in the recovery of child victims of sexual abuse in urban areas, although laws such as law number 35 of 2014 concerning child protection, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (which focuses on victims), and Law Number 39 of 1999 concerning A Human Rights (which focuses on protecting the fundamental rights of every citizen) although related regulation have been enacted to regulate the recovery of child victims of sexual abuse, family support remains essential for their rehabilitation. One important form of family support is the provision of psychological assistances, as part of the family efforts to help child victims' recovery. However, there are obstacles to families providing this support. In individualistic societies, past events may be minimized, leading to many family members to believe that recovery is not a priority for child victims. As a result, many children prefer to remain silent rather than face unsympathetic family responses. Therefore, the involvement of the government and social institutions is crucial in supporting the recovery process. Using a normative legal approach, this journal also examines how the government ensures that child victims of sexual abuse receive the necessary support, in accordance with the national legal framework governing child protection.